High-Entropy Alloys Fundamentals and Applications - Gao, Michael C.; Yeh, Jien-Wei; Liaw, Peter K.; Zhang, Yong (Springer International Publishing : Imprint: Springer, 2016)
This book provides a systematic and comprehensive description of high-entropy alloys (HEAs). The authors summarize key properties of HEAs from the perspective of both fundamental understanding and applications, which are supported by in-depth analyses. The book also contains computational modeling in tackling HEAs, which help elucidate the formation mechanisms and properties of HEAs from various length and time scales.